Legal Protection to Bank Customers Against Malware Trojan in Indonesia - Steinly Liwong (Journal of Judicial Review, 2017)
The purpose of this research is to describe clearly about the legal protection in the existing laws and regulations in Indonesia particularly about legal protection toward bank customers or consumers which domiciled in Indonesia against cybercrime which in this research focused on Malware Trojan attacks. This research also aims to know what are the rights and obligations of financial service business which in this research, financial service business known as banks who provided internet banking services so could be use by their consumers which known as bank customers. This research is using normative legal research method with qualitative data analysis method. This research is using primary data and secondary data which the data based on the library research and the interview results which only as an additional to support this research. After all data have been collected, these data will be analyzed. According to this research, it explained that the existing laws and regulations in Indonesia are not really effective to give legal protection especially for the bank customers and banks. Aside from that, banks as the financial service business and customers as the consumers are not doing their obligations which have been ruled in the existing laws and regulations in Indonesia.